2010
DOI: 10.3109/02770900903580835
|View full text |Cite
|
Sign up to set email alerts
|

The Child Asthma Link Line: A Coalition-initiated, Telephone-based, Care Coordination Intervention for Childhood Asthma

Abstract: This coalition-developed, telephone-based, system-level intervention had a significant impact on childhood asthma morbidity as measured by utilization endpoints of follow-up hospitalizations and emergency department visits. Telephone-based care coordination and service integration may be a viable and economic way to impact childhood asthma and other chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Garbutt et al (34) used telephone counseling and found that poorly controlled asthma decreased in the intervention group but saw no differences in health care use or quality of life. Coughey et al (24) assessed an asthma link line where parents or older children could call for information and referrals. They found that compared with families who did not have access to the link line, children were less likely to have hospitalizations and emergency department visits and were more likely to make primary care visits.…”
Section: Telephone Counselingmentioning
confidence: 99%
“…Garbutt et al (34) used telephone counseling and found that poorly controlled asthma decreased in the intervention group but saw no differences in health care use or quality of life. Coughey et al (24) assessed an asthma link line where parents or older children could call for information and referrals. They found that compared with families who did not have access to the link line, children were less likely to have hospitalizations and emergency department visits and were more likely to make primary care visits.…”
Section: Telephone Counselingmentioning
confidence: 99%
“…Targeting four largely African American neighborhoods with high asthma prevalence, the Philadelphia MCAN project built an integrated partnership based on 13 years of experience with two community-based asthma programs, the Community Asthma Prevention Program (CAPP) of Children’s Hospital of Philadelphia (Bryant-Stephens, Kurian, Guo, & Zhao, 2009) and the Child Asthma Link Line of the Philadelphia Allies Against Asthma Coalition (Rosenthal et al, 2006; Coughey et al, 2010). CAPP’s home visit component is adapted from three evidence-based interventions, comparable to the other care coordination programs in this article, and therefore discussed here.…”
Section: Resultsmentioning
confidence: 99%
“…Patients were successfully contacted via telephone (83.2% of patients were reached, as compared to home visit completion of closer to 45% during a pilot study in our clinic in 2005). This high level of acceptability suggests that telephone follow-up is a practical and successful way to reach patients from low-income and minority households (30).…”
Section: Discussionmentioning
confidence: 99%